(untitled) (Our Nature, 2011)
A total of 11 mistletoe species, eight belonging to five genera in the family Loranthaceae and three species belonging to two genera in the family Viscaceae were documented from 43 host species belonging to 24 unrelated host families along Tribhuvan highway, central Nepal. Wide host range of Scurrula species (Loranthaceae) showed that they were more generalist and successfully parasitized as many hosts as encountered, while Viscaceae mistletoes showed narrow host range and high degree of host specificity since they infected a limited number of hosts. The irregular and patchy distribution of mistletoe along the highway was governed by three major factors: forest structure, site mesoclimate and availability of suitable host species. Marginal fragmented forests located along the warm sunny slopes of highway were found as most suitable habitat. Warmer southern sunny slopes, between Sinbhanjyang to Bahise Dobhan, favoured wider altitudinal distribution range of mistletoe compared to cold and moist northern slopes. DOI: 10.3126/on.v8i1.4317